2010
DOI: 10.1111/j.1365-2249.2010.04154.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil membrane expression of proteinase 3 is dependent upon CD177 expression

Abstract: SummaryProteinase 3 (PR3) is a major autoantigen in anti-neutrophil cytoplasmic antibodies (ANCA)-associated systemic vasculitis (AASV), and the proportion of neutrophils expressing PR3 on their membrane (mPR3 + ) is increased in AASV. We have shown recently that mPR3 and CD177 are expressed on the same cells in healthy individuals. In this study we try to elucidate mechanisms behind the increased mPR3 expression in AASV and its relationship to CD177. All neutrophils in all individuals were either double-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 38 publications
4
46
1
Order By: Relevance
“…Experiments performed by our group, have shown that the plasma levels of mature PR3 as well as pro-PR3 are elevated in AASV [114,115,116]. It was also observed that mPR3 + neutrophils are more abundant in AASV compared to healthy donors, which agrees with previous studies suggesting that a high percentage of mPR3 + cells may be a risk factor for vasculitis [78,115].…”
Section: Recent Updatessupporting
confidence: 81%
See 1 more Smart Citation
“…Experiments performed by our group, have shown that the plasma levels of mature PR3 as well as pro-PR3 are elevated in AASV [114,115,116]. It was also observed that mPR3 + neutrophils are more abundant in AASV compared to healthy donors, which agrees with previous studies suggesting that a high percentage of mPR3 + cells may be a risk factor for vasculitis [78,115].…”
Section: Recent Updatessupporting
confidence: 81%
“…Our group has demonstrated that the mPR3 + /CD177 + neutrophil subpopulation was larger in AASV patients as compared to healthy controls, which suggests a distinct pathophysiological neutrophil phenotype in AASV [116]. Interestingly, higher CD177-mRNA, but not PR3-mRNA was found to correlate with a higher proportion of mPR3+/CD177+cells, suggesting that overproduction of CD177 could lead to an increase in the proportion of mPR3+/ CD177+neutrophils [116].…”
Section: Recent Updatesmentioning
confidence: 86%
“…This holds true also during stable remission and shows no relation to general inflammation, medical treatment or decreased renal function (Henshaw, 1994;Ohlsson, 2003). Studies by our group have shown that the levels of plasma PR3, mPR3 and pro-PR3 are all elevated in patients with AASV (Abdgawad, 2010). Also, it was observed that mPR3+ neutrophils are more abundant in AASV compared to healthy donors, which agrees with previous studies suggesting that a high percentage of mPR3+ cells may be a risk factor for vasculitis.…”
Section: Pr3 and Aasvsupporting
confidence: 80%
“…These PR3-activated DCs stimulate autoreactive Th1-type PR3-specific CD4+T cells. Our group has demonstrated that the mPR3+/CD177+ neutrophil subpopulation was larger in AASV patients as compared to healthy controls, which suggests a distinct pathophysiological basis (Abdgawad, 2010 ). mPR3 and CD177 exhibit a parallel dynamic membrane expression with rapid internalization and re-expression.…”
Section: Pr3 and Aasvmentioning
confidence: 99%
“…They all are secreted extracellularly upon neutrophil activation [8], but only PR3 is constitutively expressed on the plasma membranes of a subpopulation of resting neutrophils [9,10]. The levels of plasma PR3, proPR3 and neutrophil membrane PR3 are all elevated in patients with sepsis and AAV [10]. PR3 can enzymatically degrade the major macromolecules of extracellular matrix [8].…”
Section: Introductionmentioning
confidence: 99%